Developmental Profiling of Dietary Carbohydrate Digestion in Piglets - Gao, Xiaoqian; Yu, Bing; Yu, Jie; Mao, Xiangbing; Huang, Zhiqing; Luo, Yuheng; Luo, Junqiu; Zheng, Ping; Yan, Hui; He, Jun; Chen, Daiwen (Frontiers in Microbiology, 2022)
Carbohydrates are the main source of energy in the diet, accounting for the largest proportion in the diets of humans and monogastic animals. Although recent progress has been made in the study of intestinal carbohydrate digestion in pigs, there is a lack of comprehensive study on the dynamic changes of intestinal carbohydrate digestion with age in the early growth stage of piglets. To fill in this gap of knowledge, we collected samples of small intestinal, pancreatic tissues and colonic digesta from 42 piglets during newborn (day (d) 0), lactation (d 7,14), weaning (d 21) and nursery (d 28, 35, 42) stages. Intestinal and pancreatic tissues as well as colonic digesta were collected at necropsy and analyzed for morphology, digestive enzyme activities, short-chain fatty acids (SCFA) and microbial abundance. Villus height reached a maximum at 1 week (d 7) in the duodenum and jejunum (P < 0.01) and higher ratio of villus height to crypt depth and lactase activity were observed on d 0 and 7 (P < 0.001) compared to other ages. However, the sucrase and maltase activities were increased with piglets age. Similar activities of sucrose and maltase were found in the small intestine. Additionally, amylase, lipase and protease activities were assayed in the pancreas. The activity of amylase increased with age, while lipase and protease decreased gradually from birth to weaning (d 21, 28), and then increased after weaning (d 35, 42). Compared with the d 0, the d 42 had increased abundance of Firmicutes and Bacteroidetes with higher concentration of total SCFA (P <0.001) as well as decreased the aboundance of Proteobacteria, but weaning (d 21, 28) increased the abundance of Proteobacteria in the colon. These results indicate that with the increase of piglet age, carbohydrate digestive function gradually increased, but weaning hindered the development of intestinal function. These results provide us with new insights into healthy intestinal development in piglets, which may help us better regulate piglets' physiological health in the future.